2019
DOI: 10.1007/s13311-018-00696-y
|View full text |Cite
|
Sign up to set email alerts
|

Genetics, Mechanisms, and Therapeutic Progress in Polyglutamine Spinocerebellar Ataxias

Abstract: Autosomal dominant cerebellar ataxias (ADCAs) are a group of neurodegenerative disorders characterized by degeneration of the cerebellum and its connections. All ADCAs have progressive ataxia as their main clinical feature, frequently accompanied by dysarthria and oculomotor deficits. The most common spinocerebellar ataxias (SCAs) are 6 polyglutamine (polyQ) SCAs. These diseases are all caused by a CAG repeat expansion in the coding region of a gene. Currently, no curative treatment is available for any of the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
115
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 112 publications
(117 citation statements)
references
References 301 publications
(331 reference statements)
2
115
0
Order By: Relevance
“…Studies reported that knockdown of both mATXN3 and wtATXN3 alleles using RNAi and ASO, were a doubleedged sword to SCA3/MJD models. Therefore, strategies aimed at selective silencing mutant alleles are developing rapidly [10,15,18,19,52]. In this study, we delivered paired sgRNA/Cas9n and donor DNA as modi cation templates to achieve HR repair, which was consistent with previous HD studies [24,25,53].…”
Section: Discussionsupporting
confidence: 70%
“…Studies reported that knockdown of both mATXN3 and wtATXN3 alleles using RNAi and ASO, were a doubleedged sword to SCA3/MJD models. Therefore, strategies aimed at selective silencing mutant alleles are developing rapidly [10,15,18,19,52]. In this study, we delivered paired sgRNA/Cas9n and donor DNA as modi cation templates to achieve HR repair, which was consistent with previous HD studies [24,25,53].…”
Section: Discussionsupporting
confidence: 70%
“…The normal polyQ tract in SCA proteins is generally polymorphic in length, while beyond an apparent threshold the diseases become fully penetrant. Depending on the SCA, the pathogenic properties of the mutated protein can appear with an expansion ranging from 20 to several hundreds of glutamines (Buijsen et al, 2019). PolyQ SCAs are generally adult onset disorders and progress over 10-20 years before leading to death of patients (Klockgether, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…We focused on this apparent dysregulation of protein homeostasis in A-T cells because many of the more common neurodegenerative diseases in the human population are associated with aggregation of specific polypeptides in the brain, in some cases with clear causative links between the aggregation and neurotoxicity, and diverse model systems have confirmed these relationships (Bourdenx et al, 2017;Currais et al, 2017;Gidalevitz et al, 2006;Groh et al, 2017; Kikis et al, 2010;Ross and Poirier, 2004). In addition, several of the SCA ataxias, while associated with diverse genetic mutations, generate aggregation-prone mutant proteins that cause cerebellum-specific neurodegeneration similar to that observed in A-T (Buijsen et al, 2019;Klockgether et al, 2019).…”
Section: Introductionmentioning
confidence: 85%